Tropical Soda Apple Leaf Beetle, Gratiana boliviana Spaeth (Insecta: Coleoptera: Chrysomelidae: Cassidinae) - Rodrigo Diaz; William A. Overholt; Ken Hibbard; Julio Medal (EDIS)
Tropical soda apple is a prickly shrub native to South America that is a major problem in pastures and conservation areas. So a multi-agency program supported the rearing, distribution, and release of more than 250,000 tropical soda apple leaf beetles across Florida from 2003 to 2011. This 4-page fact sheet was written by Rodrigo Diaz, William A. Overholt, Ken Hibbard, and Julio Medal, and published by the UF Department of Entomology and Nematology, January 2013.